Statin use and survival in CLL/SLL treated with ibrutinib: pooled analysis of 4 randomized controlled trials - Ahmad Y. Abuhelwa; Sara A. Almansour; Jennifer R. Brown; Humaid O. Al-Shamsi; Ziad Abuhelwa; Zelal Kharaba; Yasser Bustanji; Mohammad H. Semreen; Salma Ali; Ahmad Alhuraiji; Ross A. McKinnon; Michael J. Sorich; et al. (Blood Advances)
Abstract: Patients with chronic lymphocytic leukemia (CLL) and small lymphocytic lymphoma (SLL) have seen significant treatment advancements with the emergence of Bruton tyrosine kinase inhibitors like ibrutinib. Statin use has been linked to reduced mortality in several cancers, including CLL. However, their concomitant use with targeted therapies such as ibrutinib remains unexplored. This study investigates the association of statin use with survival and adverse event outcomes in patients with CLL/SLL initiating contemporary treatment regimens, including ibrutinib. Individual participant data from 4 randomized trials—RESONATE, RESONATE-2, iLLUMINATE, and HELIOS—were used. Associations between baseline statin use and treatment outcomes were examined using Cox proportional hazards models for overall survival (OS), progression-free survival (PFS), and cancer-specific survival (CCS), and logistic regression models for grade ≥3 adverse effects. Analyses were adjusted for age, sex, weight, Eastern Cooperative Oncology Group performance status, disease diagnosis, bulky disease (≥5 cm), time since diagnosis, comorbidity count, and the use of beta-blockers, calcium channel blockers, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, and diuretics. Of 1467 patients, 424 (29%) were using statins. Statin use was significantly associated with improved OS (adjusted hazard ratio [aHR] 0.62 [95% CI, 0.48‑0.79], P < 0.001), PFS (aHR 0.74 [95% CI, 0.62-0.89], P = 0.001), and CCS (aHR 0.39 [95% CI, 0.22–0.70], P = 0.001). Findings were consistent across ibrutinib vs nonibrutinib treatment arms and CLL vs SLL diagnosis. No significant association with grade ≥3 adverse effects was observed. Statin use was identified as an independent positive prognostic factor in patients with CLL/SLL, irrespective of the treatment employed. Further research is needed to validate these results and explore the underlying impacts of statins in CLL/SLL. These trials were registered at www.ClinicalTrials.gov as #NCT01578707, #NCT01722487, #NCT02264574, and #NCT01611090.